Konsep Pendidikan Akhlak Siswa Madrasah Ibtidaiyah Perspetif K.H. Hasan Asy’ari - Rahman, Azibur (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to analyze the concept of moral education in Adabul 'Alim wa Muta'allim by Hasyim Asyari and its relevance in the context of contemporary education. The method used is qualitative research with a library research approach, which examines primary data sources in the form of Adabul 'Alim wa Muta'allim texts and secondary sources in the form of related literature. Data collection techniques use documentation studies, and content analysis is used to explore the moral values contained in the book. The results show that Hasyim Asyari's concept of moral education emphasizes the importance of exemplary teachers, courtesy of students, and a harmonious relationship between the two. This concept remains relevant to be applied in today's education, especially in the formation of student character based on moral and spiritual values. This research also contributes to the development of moral education in the modern education curriculum and relates Hasyim Asyari's thoughts to the challenges of education in the era of globalization.